Pemesanan Paket Wedding Organizer pada Cahaya Bridal Decoration Berbasis Web Sukabumi - Faturachman, Rifcki Aziz; Rahaningsih, Nining; Basysyar, Fadil M; Kaslani; Tohidi, Edi (MEANS (Media Informasi Analisa dan Sistem), 2022)
The Wedding Organizer package ordering information system is made by utilizing web-lined information technology, with the aim of expanding the area of promotion and sales of wedding packages and simplifying the ordering process. so the author tries to make a Final Project on the Website-Based Website-Based Information System for ordering wedding organizer packages. In the process of collecting data with the aim of solving problems, the authors use data sources (Observation and Interview). The authors Wedding Organizer package ordering information system uses the PHP and MySQL programming languages. For system design, the author uses the Prototype method. The final result obtained in this study is a website-based Information System, which can provide information about several wedding organizer packages, wedding organizer package prices and the contents of wedding organizer packages available at Cahaya Bridal Decoration. With several advantages of website technology as an information medium, the Website-Based Information System for ordering wedding organizer packages is expected to expand the reach of information dissemination to all aspects